Human metapneumovirus (HMPV): A brief overview - Ansori, Arif Nur Muhammad (PT. Mega Science Indonesia, 2025)
Human metapneumovirus (HMPV), discovered in 2001, is a significant respiratory pathogen in the Paramyxoviridae family that is responsible for substantial global morbidity and mortality. Despite its clinical impact, HMPV remains underdiagnosed and lacks specific treatments and vaccines. This perspective aims to provide a comprehensive analysis of HMPV as an emerging respiratory pathogen, examining its virological characteristics, epidemiology, clinical manifestations, pathogenesis, diagnostic methods, and management approaches. This review synthesizes the current literature on HMPV, examining its virological characteristics, epidemiology, clinical manifestations, pathogenesis, and management approaches through an analysis of peer-reviewed publications from 2001-2025. HMPV accounts for 5–10% of pediatric respiratory hospitalizations globally, with an estimated 14.2 million lower respiratory tract infections in children under five annually, resulting in 643,000 hospital admissions and 16,100 in-hospital deaths annually. The virus predominantly affects children, elderly individuals, and immunocompromised patients, who present with symptoms ranging from mild upper respiratory infections to severe pneumonia. Diagnostic advances, particularly in molecular techniques, have improved detection capabilities. Current management relies primarily on supportive care, whereas therapeutic research focuses on antiviral agents, monoclonal antibodies, and vaccine candidates utilizing novel platforms, including nanoparticle and mRNA technologies. Increased global surveillance, accelerated vaccine development, and novel therapeutic approaches are needed to address HMPV. Research priorities include understanding long-term immunity, immune evasion mechanisms, and the environmental influences on transmission. Collaborative efforts among academia, industry, public health institutions, and regulatory bodies are essential to translate scientific discoveries into effective interventions that reduce the public health burden of HMPV.